Surface and solution properties of anionic/nonionic surfactant mixtures of alkylbenzene sulfonate and triethyleneglycol decyl ether. - Tucker, I; Penfold, J; Thomas, R; Dong, C; Golding, S; Gibson, C; Grillo, I (2010)
The surface adsorption behavior and the solution microstructure of mixtures of the C(6) isomer of anionic surfactant sodium para-dodecyl benzene sulfonate, ABS, with nonionic surfactant monodecyl triethyleneglycol ether, C(10)E(3,) have been investigated using a combination of neutron reflectivity, NR, and small-angle neutron scattering, SANS. In solution, the mixing of C(10)E(3) and ABS results in the formation of small globular micelles over most of the composition range (100:0 to 20:80 ABS/C(10)E(3)). Planar aggregates (lamellar or unilamellar vesicles, ULV) are observed for solution compositions rich in the nonionic surfactant (>80 mol % nonionic). Prior to the transition to planar aggregates, the micelle aggregation number increases with increasing nonionic composition. The lamellar-phase region is preceded by a narrow range of composition over which mixtures of micelles and small unilamellar vesicles coexist. The variation in surface absorption behavior with solution composition shows a strong surface partitioning of the more surface-active component, C(10)E(3). This pronounced departure from ideal mixing is not readily explained by existing surfactant mixing theories. In the presence of Ca(2+) ions, a more complex evolution of solution phase behavior with solution composition is observed. The lamellar-phase region occurs over a broader range of solution compositions at the expense of the small-vesicle phase. The phase boundaries are shifted to lower nonionic compositions, and the extent to which the solution-phase diagrams are modified increases with increasing calcium ion concentration. The SANS data for the large planar aggregates are consistent with large polydisperse flexible unilamellar vesicles. In the presence of Ca(2+) ions, the surface adsorption patterns become more consistent with ideal mixing in the nonionic-rich region of the surface-phase diagram. However, in the ABS-rich regions the surface behavior is more complex because of the spontaneous formation of more complex surface microstructures (bilayers to multilayers). Both in water and in the presence of Ca(2+) ions the variations in the surface adsorption behavior and in the solution mesophase structure do not appear to be closely correlated.